Pathological assessment of farmed yellowtail tetra Astyanax altiparanae infested by Acusicola sp. (Ergasilidae) - Pádua, Santiago Benites De; Jerônimo, Gabriela Tomas; Menezes-Filho, Roney Nogueira De; Taboga, Sebastião Roberto [UNESP]; Martins, Maurício Laterça; De Andrade Belo, Marco Antonio [UNESP] (Elsevier, 2015)
This study registers for the first time the copepod Acusicola sp. infesting the gills of farmed yellowtail tetra Astyanax altiparanae, as well as new information on gross pathology and gill alterations. Five specimens of yellowtail tetra showing slow swimming, respiratory difficulty, scaleness and darkened skin were examined. Fish were analysed in situ for ectoparasites diagnosis. Fragments of the gill arches were removed and processed according to usual histopathology. The gills showed focal and multifocal paleness and whitish areas besides the congestion and hemorrhage signs on the gill filaments. Several white spots attached to the gill filament apex with slight movement were identified as the ergasilid crustacean. Histopathological analysis revealed the gill and blood vessels compression. It was also observed proliferative alterations close to gill filament apex, hyperplasia, total fusion and subepithelial oedema of the secondary lamellae, proliferation of the mucus cells, and inflammatory infiltrate by eosinophilic granular cells surrounding the parasite attachment region. The best management practices and the implementation of diagnostic program are also discussed.
Keywords: Copepoda; Fish; Gills; Histopathology; Pathogenesis